Dynamics of precision-guided projectile launch: fluid–structure interaction - Verberne, P.; Meguid, S. A. (Acta mechanica, 2021)
Precision-guided projectiles (PGPs) experience severe shock loads during launch emanating from the propellant gases and the surrounding air. The complex flow environment that exists within the confined space of the barrel and at muzzle exit is significantly influenced by the speed of the projectile, the compressibility of the air, and the rapid state transition of the projectile from the confined volume of the barrel to the surrounding free space. In this effort, we extend our earlier vacuum work (Yin et al. in Int J Mech Mater Des 10:439–450. https://doi.org/10.1007/s10999-014-9255-0 , 2014) by performing comprehensive and a more realistic multiphysics simulations of the dynamics of the entire launch process of a projectile accounting for the intense combustion pressures of the propellant, the large accelerations experienced during the launch, and the induced shock waves. Our numerical model successfully captured the development and progression as well as the interaction of the projectile with the induced shock waves. Specifically, the model identifies the intense pressures generated by the propellant that result in supersonic flow conditions within the confined space of the barrel. This supersonic flow within the barrel leads to a wave front that travels ahead of the projectile creating a normal shock wave in the barrel. Once the normal shock crosses the muzzle exit, it diffracts into three types of shock waves: precursor, bow, and base. These shock loads pose a significant threat to the embedded electronic systems (EES) necessary for the operation, guidance and control of these PGPs. Our model further reveals that the projectile will experience a reduction in velocity as a result of induced frictional drag and interaction with the induced shock waves. This study will assist in the design and development of appropriate encapsulation techniques necessary for the protection of EES.